Neuroinflammation modulation by 5-aminosalicylic acid - Silva, Ana Alexandra Flores da (2022)
The central nervous system (CNS) is a highly complex and unknown structure of the human body, which has been the object of constant study and monitoring. Mainly by the neuronal circuits of the CNS and their functions frequently compromised, associated with pathologies such as Parkinson's Disease (PD). PD is the second most prevalent neurodegenerative disorder, characterized by the loss of dopaminergic neurons (DN) in the substantia nigra pars compact (SNpc), with subsequent loss of dopamine (DA) in the striatum (ST) and by the accumulation of dystrophic projections composed of a- synuclein. For an in-depth study of this pathology, several animal models were designed to reproduce the main behavioral dysfunctions and cellular pathological mechanisms associated with PD, being lipopolysaccharide (LPS) induced neuroinflammation model one of the most used pathology's reproduction pathways. Previous studies have revealed that pro-inflammatory cytokines are a strong indicator of the neuroinflammatory state, as they are key molecules that modulate immune responses and, after repeated administration of LPS, changes in their levels are observed. However, doses and administration routes of LPS are relevant factors to be considered, generating different responses for the same model. Thus, the first part of this study aimed to reproduce the model of neuroinflammation induced by LPS, by administering this molecule via the intraperitoneal route, in mice. However, as PD symptomatically, in addition to translating into behavioral disorders, is also reported by gastrointestinal involvement, an anti-inflammatory commercially called mesalazine was used to evaluate its neuroprotective effect in the model. animal of previously induced neuroinflammation. This study was carried out using behavioral assessments, the assessment of immunoreactivity to tyrosine hydroxylase (TH), the assessment of changes in microglial and astrocytic activity, and the quantification of the levels of pro-inflammatory interleukins (IL) in different brain areas.